Exploring the structure and properties of $$α$$ -sheet based bilayer borophenes - Subrata Rakshit; Nevill Gonzalez Szwacki (Scientific Reports)
Abstract Recent experimental realizations of bilayer boron materials motivated us to study the structure and properties of $$\alpha$$ -sheet-based bilayer borophenes with interlayer covalent bonds. As shown here, at least three stacking variations are possible: AA, AB, and $$\hbox {AB}'$$ . The on-top AA-stacking has been obtained experimentally supported on a metallic substrate. The AB-stacking is the most stable among neutral freestanding structures, whereas the AA and $$\hbox {AB}'$$ stacking sequences are very close in energy, both for neutral and negatively charged cases. The studied bilayer borophenes exhibit extraordinarily high electric conductivity with values as high as $${\sim } 10^7\mathrm {~S}/\textrm{m}$$ for the experimentally observed AA-stacking. The highly stable AB-stacking bilayer, reported here for the first time, exhibits an anisotropic conductivity with an average value of $$6.0 \times 10^6~\mathrm {~S}/\textrm{m}$$ . Contrary to the AA-stacking bilayer that retains the 6-fold fold rotational symmetry of the $$\alpha$$ -sheet, the AB-stacking structure has 2-fold symmetry, which leads to the anisotropic transport properties.